Examining the tapestry of mental health crises in low- & middle-income countries: an intercontinental analysis of the contributing factors and instructive approaches" - Naeem Mubarak; Sabba Kanwal; Fatima Rahman Rana; Saba Tariq; Sundus Tariq; Mohamed Hassan Elnaem; Asad Majeed Khan (Journal of University Medical & Dental College, 2023)
In recent decades, the intricate landscape of mental health challenges has become a focal point of global concern, with particular urgency in Low- and Middle-Income Countries (LMICs). This manuscript delves into the multidimensional tapestry of mental health issues prevalent in these regions, offering an intercontinental analysis that seeks to unravel the contributing factors and proposes strategies for improvement. Through a meticulous examination of diverse sociocultural, economic, and healthcare-related variables, this study aims to provide a comprehensive understanding of the complex dynamics shaping mental health crises in LMICs. Through an intercontinental lens, our analysis aims to transcend geographical boundaries, examining the commonalities and distinctions inherent in the mental health landscapes of LMICs. This inquiry is driven by a dual commitment: to comprehensively understand the determinants of mental health challenges and to identify instructive approaches that can serve as foundations for targeted interventions. In navigating this intellectual terrain, our study not only strives to contribute to the academic discourse on global mental health but also aspires to inform policy and practice, fostering a nuanced understanding of mental health dynamics and cultivating evidence-based strategies to ameliorate the burden faced by individuals in LMICs. By synthesizing current research, empirical data, and theoretical frameworks, our exploration not only illuminates the challenges but also endeavors to identify instructive approaches for mitigating the impact of mental health issues in resource-constrained settings. The confluence of factors influencing mental health in LMICs demands an interdisciplinary lens, and this manuscript endeavors to navigate this intricate terrain with rigor and precision. This article exposes the significant gap in mental health services, attributing this disparity to limited public funding, insufficient allocation for children and adolescents, and an inadequate distribution of funds in mental health infrastructure. The scarcity of mental health workers, particularly in primary healthcare settings, further exacerbates the problem. The contributing factors to mental health crises in LMICs include ineffective legislation, leadership, and national health policies, as well as cultural beliefs and stereotypes. The lack of a mental health information system further hampers meaningful progress in these regions. There is a need for a comprehensive mental health system that considers cultural, social, and economic factors unique to LMICs. To address the challenges faced by LMICs, the article suggests strategies, including legislative reforms, policy development, public education to reduce stigma, and promotion of evidence-based interventions. By drawing on existing principles and considerations, the authors provide a specific system of mental health services grounded in community-based care and "mental health-in-all-policies" approach which advocates for rational investment allocations, considering social determinants, prevalence data, and the humane treatment of individuals with mental health issues in these regions.